Investigation of fine and coarse particulate matter from burning areas in Chiang Mai, Thailand using the WRF/CALPUFF - Teerachai Amnuaylojaroen (2018)
The WRF/CALPUFF modeling system has been performed to investigate PM2.5 distributions and relative contribution of fine fraction (PM2.5) and coarse fraction (PM10-2.5) to PM10 fraction from forest fires in Chiang Mai basin in March 2007. The strong atmospheric stability and low level light wind over the Chiang Mai basin were the favorable conditions for the particulate matter accumulation. The distributions of simulated PM2.5 were mostly close to the burning areas. Model results indicated that the daily average concentrations of the PM10 and PM2.5 in March 2007 were in the range of 73-300 μg/m3and 32.1-203.5 μg/m3, respectively which frequently exceeded Thai and overseas standards. About 74% and 26 % of the PM10 consist of the PM2.5 and PM10-2.5 contributions, respectively. The PM10 concentrations are more strongly associated with PM2.5 concentrations compared to that of PM10-2.5 due to higher contribution of the PM2.5.